Contextualising contextualism: general reflections on the communitaris - liberal debate - Giusti Hundskopf, Miguel (Estudios de Filosofía, 1994)
The intention of the present analysis is to show the inherent limits of liberal civilisation as a source of ideas for moral philosopby. The collapse of socialism apparently confirmed liberalism in its stance. Not with standing it has continued to receive criticism from within on the part of communitarists. Communitarists criticise the effects of social disruption and ideological cover-up concerning the crude reality the individual has to bear in a market economy. Three main critical issues are tackled: individualism, moral formalism and indifference as to the communitary mould of human life. Nevertheless, liberalism does posses a strong asset: it fosters and facilitates the search of cross-country and intercultural human relations where mutual recognition becomes more equitable, since it safeguards the legal democratic state without sacrificing cultural pluralism.